Efficacy and safety of the biosimilar ABP 215 compared with Bevacizumab in patients with advanced nonsquamous non-small cell lung cancer (MAPLE): a randomized, double-blind, phase III study - Thatcher, Nicholas; Thomas, Michael (Clinical cancer research, 2019)
Purpose: This phase III study compared clinical efficacy and safety of the biosimilar ABP 215 with bevacizumab reference product (RP) in patients with advanced nonsquamous non-small cell lung cancer (NSCLC). - Patients and Methods: Patients were randomized 1:1 to ABP 215 or bevacizumab 15 mg/kg every three weeks for 6 cycles. All patients received carboplatin and paclitaxel every three weeks for ≥4 and ≤6 cycles. The primary efficacy endpoint was risk ratio of objective response rate (ORR); clinical equivalence was confirmed if the 2-sided 90% confidence interval (CI) of the risk ratio was within the margin of 0.67 to 1.5. Secondary endpoints included risk difference of ORR, duration of response (DOR), progression-free survival (PFS), and overall survival (OS); pharmacokinetics, adverse events (AEs), and incidence of antidrug antibodies (ADAs) were monitored. - Results: A total of 820 patients were screened; 642 were randomized to ABP 215 (n = 328) and bevacizumab (n = 314). Overall, 128 (39.0%) and 131 (41.7%) patients in the ABP 215 and bevacizumab groups, respectively, had objective responses [ORR risk ratio: 0.93 (90% CI, 0.80-1.09)]. In the ABP 215 and bevacizumab group, 308 (95.1%) and 289 (93.5%) patients, respectively, had at least 1 AE; 13 (4.0%) and 11 (3.6%) experienced a fatal AE. Anti-VEGF toxicity was low and comparable between treatment groups. At week 19, median trough serum drug concentration was 132 μg/mL (ABP 215 group) and 129 μg/mL (bevacizumab group). No patient tested positive for neutralizing antibodies. - Conclusions: ABP 215 is similar to bevacizumab RP with respect to clinical efficacy, safety, immunogenicity, and pharmacokinetics. The totality of evidence supports clinical equivalence of ABP 215 and bevacizumab.